Evaluation of the Implementation of Guidance at Sports Public Senior High School Lampung (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2019)
This study aims to evaluate antecedents which covering background, and planning coaching programs at Sports Public Senior High School Lampung, evaluating the transactions that include recruitment of trainers, athletes, training programs, supporting facilities and infrastructure, funding, consumption, coordination, and welfare coaching athlete, and evaluates outcomes which include the successful implementation of coaching in the achievements of athletes at Sports Public Senior High School, Lampung. This study used a descriptive qualitative approach with a Countenance evaluation model from Robert E. Stake. The subjects in this study were administrators, trainers, and athletes at Sports Public Senior High School Lampung. The results of this study are antecedent evaluation consisting of background and planning of the coaching program at Sports Public Senior High School Lampung is clear and structured well, evaluation of transactions consisting of recruitment coaches and athletes has gone well, the implementation of the coaching program is quite reasonable according to scheduled training programs, inadequate facilities and some infrastructure have not been of national standard, funding is running poorly not enough to meet the needs of coaching, consumption is still not good enough to meet the needs of athletes, coordination has gone well, welfare given to coaches and athletes is still lacking and not yet maximal, and outcomes evaluation in the form of athletes' achievements in several sports has been quite good but not yet stable and there are still sports that have not however achieved.